Research on billet optimization and forming influence rule of shaft forging - YIN Ranhao; LIU Dong; CHEN Jingqing; HAN Shun; WANG Chunxu; LI Yong; WANG Jianguo (Xibei Gongye Daxue Xuebao, 2023)
In this paper, DEFORM-2D numerical simulation software is used to simulate the forming process parameters of C250 steel. Through the optimization of the metal flow law of the billet in the extrusion forming process and the strain evolution law of the strain zone of the big end, small end and rod in the extrusion process, studied on shape and extrusion ratio (lambda), lower die cone Angle (α4) initial temperature, extrusion speed (v), block (T0) and the sizing zone length (H2) for the peak load, forgings at the top of the building size Z strain zone width X, small head, big head end diameter end strain zone length, stem region Y strain uniformity, outlet temperature uniformity and forging parts where the head end set the influence law of temperature uniformity. Finally, the experiment is verified.